Late-Stage Difluoromethylation of Aliphatic Carboxylic Acids with Copper Catalysis - Yan, Wenhao; Paeth, Matthew; Zacate, Samson; Zeng, Xiaojun; Liu, Wei (Synlett, 2020)
Difluoromethyl groups are of great importance to synthetic and pharmaceutical chemistry because of their unique properties that regulate molecular bioactivity. In this article, approaches towards difluoromethylation are discussed and the development of the first aliphatic decarboxylative difluoromethylation reaction is detailed. With a broad scope, the real-world utility of the protocol is demonstrated.
Keywords: difluoromethylation; decarboxylative; copper catalysis; redox active ester; radicals